Karakteristik Perusahaan dan Eksekutif dalam Memprediksi Penghindaran Pajak di Indonesia - Erika, Lidwina; Carolina, Verani (Studi Akuntansi dan Keuangan Indonesia, 2023)
The purpose of this research is to investigate whether certain company characteristics, such as firm size, leverage, liquidity, profitability, and executive traits, are connected to the tax avoidance strategies utilized by companies. This study utilizes a quantitative research method and examines secondary data from the years 2013 to 2022. The sample is chosen using a purposive sampling technique. Data analysis is carried out using the panel data regression method in Eviews 12 software. The findings of the study indicate that firm size, leverage, profitability, and executive traits have an impact on tax avoidance, while liquidity does not significantly affect tax avoidance. The results of this research will help investors make decisions by evaluating companies known to engage in tax avoidance based on their size, leverage, profitability, and the characteristics of their executives. However, it is important to note that this research does not consider specific industry characteristics and cannot identify the tax avoidance tendencies within each industry. Hence, future research is recommended to include control variables for different industry groups.